A Stimuli‐Responsive Metallohydrogel Exhibiting Cyclohexane‐Like Hydrophobicity. Issue 12 (16th May 2017) - Laishram, Raju; Maitra, Uday
Abstract: Silver(I) forms a hydrogel in the presence of cholate with unusual properties, which are not observed with other cations. Polarity‐sensitive probes have shown that the spherical aggregates observed in the gel have 'pockets' with hydrophobicity comparable to that of degassed cyclohexane. The gel exhibited thermo‐ and mechanoresponsive properties. Color tunability from blue to cyan and green was observed with prodan. The two sol phases of the gel formed by applying stress and temperature showed very different properties. Abstract : Silver cholate gels have pockets whose hydrophobicity is similar to that of degassed cyclohexane. The gels also show thermo‐ and mechanoresponsive properties, which were studied using fluorescence probes.